One year into the COVID‐19 pandemic: What do we know so far from studies assessing risk and mitigation of droplet aerosolisation during endonasal surgery? A systematic review. (14th September 2021) - Williams, Stephen P.; Leong, Samuel C.
Abstract: Objectives: As we pass the anniversary of the declaration of a global pandemic by the World Health Organisation, it invites us to reflect upon the inescapable changes that coronavirus has wrought upon ENT and, in particular, rhinological practice. As it remains unclear when we will emerge from the shadow of COVID‐19, a critical analysis of the evidence base on both the assessment and mitigation of risk is vital for ENT departments worldwide. This article presents a systematic review of the literature examining articles which consider either the quantification of risk or strategies to mitigate risk specifically in the setting of rhinological surgery. Design: Systematic literature review. Results: The literature search yielded a total of 3406 returns with 24 articles meeting eligibility criteria. A narrative synthesis stratified results into two broad themes: (1) those which made an assessment as to the aerosolisation of droplets during sinus surgery, further sub‐divided into work which considered macroscopically visible droplets and that which considered smaller particles; (2) and those studies which examined the mitigation of this risk. Conclusion: Studies considering the aerosolisation of both droplets and smaller particles suggest endonasal surgery carries significant risk. While results both highlight a range of innovative adjunctive strategies and support suction as an important intervention to reduce aerosolisation, appropriate use of personal protective equipment (PPE) should be considered mandatory for all healthcare professionals involved in rhinological surgery. Studies have demonstrated that close adherence to PPE use is effective in preventing COVID‐19 infection.